A gift programme for sustainable forest management? A Swiss perspective on public policies and property rights. - Creutzburg, Leonard; Ohmura, Tamaki; Lieberherr, Eva (Copernicus Publications, 2020)
For multifunctional forests that seek to fulfil societal, environmental and economic demands, active forest management is key. However, like in many other western European countries, Switzerland's small-scale private forest owners increasingly do not manage their forests. By applying and adapting the Institutional Resource Regime (IRR), a framework for environmental policy analysis that considers use rights both from public policies and property rights, we analyse the situation in Switzerland. Subsequently, we propose a Swiss forest gift programme – based on the Canadian Ecological Gifts Program (EGP) – consisting of different policy instruments that would ultimately lead to a transfer of property rights from the current to new owners. In sum, the authors argue that the proposal would lead to more “coherence”, with regard to the IRR's sustainability dimension, and consequently to clearer responsibilities for the sustainable management of forests in Switzerland.
Keywords: Forstwirtschaft; Forstverwaltung; Waldentwicklung; Förderprogramm; Nachhaltige Entwicklung